Ecologia da paisagem e controle biológico conservativo na cultura da cana-de-açúcar - Ferraz, Mayara Silva Oliveira (2022)
Agricultural expansion has advanced towards natural environments, causing changes in the landscape and interfering with important ecosystem processes on which agriculture and food production depend. As a result, different proportions of connectivity are found between agricultural areas and areas with native vegetation, which interferes with natural biological control. The sugarcane crop harbors several species of insects that can cause economic losses, most of which are still controlled by chemical products. Despite this, in Brazil this culture has the largest biological control program in the world. In view of the above, this work aimed to carry out a survey of insects in sugarcane fields with different landscape compositions; indicate the best color and trap to be used in the sugarcane crop; to evaluate the influence of different landscape compositions on the richness, abundance and diversity of natural enemies in the sugarcane agroecosystem and to evaluate the influence of different environmental variables on the insect community. For this, collections were carried out with different colors of traps to see which one attracts more insects in the sugarcane field and also using the pitfall trap to verify if this insect captures in the sugarcane field. pantrap” and “pitfall” in different landscape compositions, observing if there is a difference in the community of these insects, aiming to better understand the influence of the landscape and its impact on the sugarcane culture. It was found that the yellow “pantrap” captures more insects of different orders than the white and transparent colors in the sugarcane field. Pitfall traps were also efficient in capturing insects in the sugarcane field. It was concluded that the period of dry or rainy collection influences the diversity, abundance and richness of the insects found; in the dry season there was a greater diversity and richness of natural enemies, but in the rainy season there was greater abundance. It was found that the sugarcane field with forest as surrounding vegetation in the rainy season had greater diversity and richness of natural enemies than the sugarcane field with other surrounding areas. It was concluded that all environmental variables influence the insect community present, however the season is the one that most influences; but the surrounding vegetation also influences the insect community. This reinforces that we must collect with different surrounding vegetation and also collect in these vegetations at different time.